Կարինե Խոդիկյանի արձակի պոետիկան - Ավանեսյան, Արմեն (Արմավ հրատ.)
Karine Khodikyan’s prose is one of the remarkable aspects of independence literature. In her stories, the narrator was more emphasized, who was the dictator of the plot and actions. The author’s special attention to the issue of women’s liberation is noticeable. Preserving the identity of the style,the writer enriches his stories by combining a special story plot. Mysticism and magic were often associated with biodiversity . At the same time, the vulnerable questions of today’s reality and time are depicted. The writer freely expresses her attitude towards time. Karine Khodikyan articulates today’s hero, today’s history with her stories and becomes the annals of our days. Карине Ходикян - одно из самых замечательных произведений литературы независимости. В ее рассказах больше подчеркивался рассказчик, диктующий сюжет и действия. Заметно особое внимание автора к проблеме женского раскрепощения. Сохраняя самобытность стиля, писатель обогащает свои рассказы, сочетая особый сюжет. Мистика и магия часто идут параллельно с жизнью. В то же время изображены уязвимые вопросы сегодняшней реальности и времени. Писатель свободно выражает свое отношение ко времени. Карине Ходикян своими рассказами излагает сегодняшнего героя, сегодняшнюю историю и становится летописцем наших дней.
Keywords: Գրականագիտություն